2016
DOI: 10.1016/j.math.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between a physiotherapist and an orthopaedic surgeon regarding management and prescription of corticosteroid injection for patients with shoulder pain

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Participant numbers varied from 30 to 383 (age range 15-85 years, mean age (where available) ranging from 46.2 to 67 years). The majority of studies included patients with one or two problem areas; knee [70,73], hip and knee [20,68,71], shoulder [67,69,72], shoulder or knee [66], shoulder, knee or spinal [19], with two studies having a broader inclusion of musculoskeletal or orthopaedic conditions [24,57,58,67].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participant numbers varied from 30 to 383 (age range 15-85 years, mean age (where available) ranging from 46.2 to 67 years). The majority of studies included patients with one or two problem areas; knee [70,73], hip and knee [20,68,71], shoulder [67,69,72], shoulder or knee [66], shoulder, knee or spinal [19], with two studies having a broader inclusion of musculoskeletal or orthopaedic conditions [24,57,58,67].…”
Section: Search Resultsmentioning
confidence: 99%
“…Certainty of evidence was largely constrained. Two RCTs and three cohort studies had low to unclear risk of bias [23,24,57,58,[67][68][69], and seven cohort studies had unclear risk of bias [19,20,66,[70][71][72][73]. One study [19] provided inadequate information and reported incomplete data.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…Gwet [24] and Shankar and Bangdiwala [28] compared some measures and showed that AC 1 has better properties than other kappa-type measures. In addition, AC 1 has been utilized in the field of medical research over the past decade [29][30][31][32][33][34][35]. However statistical inference procedures of AC 1 have not been discussed sufficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Shanker and Bangdiwala compared Cohen's κ, Scott's π, Prevalence Adjusted Bias Adjusted Kappa (PABAK) [26], AC 1 and B-statistic [27], which is not a kappa-type chance-corrected measure, in the case of two raters and binary outcomes and showed that AC 1 has better properties than other kappa-type measures [28]. In addition, AC 1 has been utilized in the field of medical research over the past decade [29][30][31][32][33][34][35]. Therefore, in this study we have limited our discussion to AC 1 in the case of two raters with binary outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it provided some early suggestion that SSNBs delivered by PTs might be as effective as those provided by medical doctors. A recent study comparing the efficacy of PTs providing steroid injections (in this case, to the subacromial region of the shoulder) with that of medical doctors reported equivocal outcomes (Marks et al, ). Research that tests the effectiveness of adding SSNBs to PT‐led exercise for persistent shoulder pain is needed.…”
Section: Discussionmentioning
confidence: 99%